Associations between emotions and psychophysiological states and confirmation bias in question formulation in ongoing simulated investigative interviews of child sexual abuse - Segal, Aleksandr; Bakaitytė, Aistė; Kaniušonytė, Goda; Ustinavičiūtė-Klenauskė, Laura; Haginoya, Shumpei; Zhang, Yikang; Pompedda, Francesco; Žukauskienė, Rita; Santtila, Pekka (Frontiers in Psychology, 2023)
In forensic settings interviewers are advised to ask as many open-ended questions as possible. However, even experts may have difficulty following this advice potentially negatively impacting an investigation. Here, we sought to investigate how emotions and psychophysiological parameters are associated with question formulation in real time in an ongoing (simulated) child sexual abuse (CSA) interview. Psychology students (N = 60, Mage = 22.75) conducted two interviews with child avatars, while their emotions (anger, sadness, disgust, surprise and relief), GSR and heart rate (HR) were registered. First, we found that general emotionality related to CSA and perceived realness of the avatars was associated with stronger overall emotional reactions. Second, we found that closed (vs. open) questions were preceded by more facially observable anger, but not disgust, sadness, surprise or relief. Third, closed (vs. open) questions were preceded by higher GSR resistance and lower heart rate. Results suggest for the first time that emotions and psychophysiological states can drive confirmation bias in question formulation in real time in CSA